Analysing lighting spectrum design in enhancing human well-being - Ming Yang Wong; Safial Aqbar Zakaria (ARTEKS : Jurnal Teknik Arsitektur)
Lighting design plays an essential role in interior design which it will affect human health and wellbeing physically and biologically. Therefore, this research was to analysing lighting spectrum design in enhancing human well- being. The research will be carried out in qualitative form which will study the interior of the commercial building and analysis the lighting design of it in terms of lighting spectrum and suggest the way to improve after study similar research. The problem statements in this research are limited understanding of the specific knowledge gaps related to lighting spectrum, limited access to resources and training related to lighting design, and the low comfort level of lighting spectrum design to human. This research aims to identify the inadequate or adequate of the lighting design in commercial buildings in terms of lighting spectrum, and to propose proper lighting spectrum design for commercial buildings based on the study of the selected building or interior. There was research carried out to study interior lighting design failure in residential buildings and its reasons instead of commercial building. Thus, identify the inadequate or adequate of the lighting design in commercial buildings and the way to improvement in terms of lighting spectrum will be the main part in this research. The research findings will identify the effects when public expose under inadequate or adequate interior lighting design, and the suggestions improvement for lighting design in terms of lighting spectrum that improve human wellbeing. These findings will guide the public or researchers to create better lighting design.